2015
DOI: 10.1038/ncb3143
|View full text |Cite|
|
Sign up to set email alerts
|

Independent and coordinate trafficking of single Drosophila germ plasm mRNAs

Abstract: mRNA localization is a conserved mechanism for spatial control of protein synthesis, with key roles in generating cellular and developmental asymmetry. While different transcripts may be targeted to the same subcellular domain, the extent to which their localization is coordinated is unclear. Using quantitative single molecule imaging, we analyzed the assembly of Drosophila germ plasm mRNA granules inherited by nascent germ cells. We find that the germ cell-destined transcripts nanos, cyclin B, and polar granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
296
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(343 citation statements)
references
References 54 publications
(59 reference statements)
47
296
0
Order By: Relevance
“…As shown in Figure 3C, there was a high degree of overlap between the two colors in the germline, but hardly any puncta were observed in the follicle cell layer with either of the fluorophores. Similarly, another germline specific mRNA, nanos, was detected almost exclusively in the nurse cells; however, no apparent colocalization was observed between the nos18×-Atto633 and osk17×-Atto565, consistent with previous observations (Little et al 2015) indicating specificity of these probe sets (Fig. 3D).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…As shown in Figure 3C, there was a high degree of overlap between the two colors in the germline, but hardly any puncta were observed in the follicle cell layer with either of the fluorophores. Similarly, another germline specific mRNA, nanos, was detected almost exclusively in the nurse cells; however, no apparent colocalization was observed between the nos18×-Atto633 and osk17×-Atto565, consistent with previous observations (Little et al 2015) indicating specificity of these probe sets (Fig. 3D).…”
Section: Resultssupporting
confidence: 80%
“…3A) to that of a set of 45 chemically labeled, conventional smFISH probes (osk3P (45×)-633, Fig. 3B) previously used in smFISH assays (Little et al 2015). We found that our Atto633 labeled probe set-although it contained only 42 different oligonucleotide species-provided a slightly brighter signal than the reference osk3P(45×)-Atto633 set (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations